Targeted therapy to annihilate the immune-evading phenotype in cancer evolution - Fernandez, Ariel (2018)
Cancer is a moving target, and targeted therapy must ultimatelydeal with the evolution of the disease. This is becauseevolution is the substrate for development of resistance totargeted therapy. A successful therapeutic strategy is onethat can tackle and ultimately eliminate the evading phenotype.Thus, to steer cancer evolution for therapeutic purposes,one must first note that targeted therapy imposes selectionpressure and resistant phenotypes prevail in a context ofclonal heterogeneity. The quest for complete cure makes itimperative to control the evolutionary fate of the tumor.We focus on the problem of cornering the evolving phenotypepromoted by T cell checkpoint blockade. Theseantibodies unleash the anti-tumor adaptive immune responseby blocking an off-switch T-cell receptor whose natural ligandis secreted by the tumor. In this way, checkpoint blockers turnoff the negative signal in tumor-induced immunosuppression.This immunotherapy constitutes possibly the most auspiciousanticancer treatment to date. In this context, cancer evolutionresults in immunoediting, and the evolving phenotype may besteered by targeting signaling pathways that control the modulationof the adaptive immune response, as shown in thiseditorial.